2022
DOI: 10.1111/1748-5967.12612
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of chigger mites in the Republic of Korea

Abstract: after first online publication: scientific name 'Eushoengastia koreaensis' has been corrected to 'Euschoengastia koreaensis' throughout the article and in figures 3 and 5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Clearly, the COI gene provided the greatest resolution among the specimens analysed here with no haplotypes in common between countries, whereas both ITS2 and 18S exhibited shared haplotypes in two of the three countries. To the best of our knowledge, only one other analysis of the ITS2 region in chiggers has been published, and this found no evidence of intraspecific variation in the genera Leptotrombidium , Neotrombicula , and Euschoengastia in South Korea [ 32 ], although the geographic extent of sampling was very limited. Regarding the application of 18S rRNA sequencing in chiggers, it has been used for confirmation of species identification in studies from Brazil [ 92 ] and South Korea [ 93 ], in which the gene was found to be invariant within species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the COI gene provided the greatest resolution among the specimens analysed here with no haplotypes in common between countries, whereas both ITS2 and 18S exhibited shared haplotypes in two of the three countries. To the best of our knowledge, only one other analysis of the ITS2 region in chiggers has been published, and this found no evidence of intraspecific variation in the genera Leptotrombidium , Neotrombicula , and Euschoengastia in South Korea [ 32 ], although the geographic extent of sampling was very limited. Regarding the application of 18S rRNA sequencing in chiggers, it has been used for confirmation of species identification in studies from Brazil [ 92 ] and South Korea [ 93 ], in which the gene was found to be invariant within species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of molecular barcoding based on the mitochondrially encoded cytochrome c oxidase subunit I (COI) gene [or occasionally the nuclear-encoded internal transcribed spacer 2 (ITS2) region] is becoming more widespread in the chigger field, with several studies from Asia and Europe using this approach for Leptotrombidium spp. and a number of other genera [ 30 , 31 , 32 , 33 , 34 , 35 ]. Although such analyses should be interpreted with caution since they are based on a single gene, they indicate that some chigger species with identical barcodes can display morphological plasticity on different hosts, whereas other species exhibit polymorphisms in the COI region without accompanying morphological variation.…”
Section: Introductionmentioning
confidence: 99%
“…The installed trap was recovered after 24 h, and the chigger mites were obtained from the captured wild rodent and transferred to a 2 mL vial containing 70% ethanol. Using the method reported by Lee and Choi (2022), the bodily fluid of chigger mites was extracted and used for molecular experiments, whereas the mite body from which the fluid was extracted was used for morphological species identification (Ree 1990; Ree et al . 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Although chigger mites are classified according to the classification key established by Ree (1990), they are easily damaged because of their small size, they exhibit natural variation, and they can only be classified and identified at the larval stage, owing to the morphological similarity of adults (Lee & Choi 2022). Indeed, the presence of morphologically similar species can lead to misidentification (Alves et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of molecular barcoding based on the mitochondrially-encoded cytochrome c oxidase subunit I (COI) gene [or occasionally the nuclear-encoded internal transcribed spacer 2 (ITS2) region] is becoming more widespread in the chigger eld, with several studies from Asia and Europe using this approach for Leptotrombidium spp. and a number of other genera [31][32][33][34][35]. Although such analyses should be interpreted with caution since they are based on a single gene, they indicate that some chigger species with identical barcodes can display morphological plasticity on different hosts, whereas other species exhibit polymorphisms in the COI region without accompanying morphological variation.…”
Section: Introductionmentioning
confidence: 99%